COMPOSITIONAL EVOLUTION OF MESOZOIC BASALTS IN NORTHERN TRANSBAIKALIA - Stupak F.M. (My University, 2001)
The first critical review of geological and petrochemical materials based on the author's data is presented for the Mesozoic mafic rocks of northern Transbaikalia. The rocks are demonstrated to be localized within a series of volcanic areas produced during five episodes of volcanic activity: T, J, J3-K1, K1, and K2. The petrochemistry of the rocks is examined with the use of 361 analyses. It is established that the associations of intermediate-mafic rocks of each of the volcanic stages are similar and consist of differentiated basalt - trachyte series. The Mesozoic mafic rocks of northern Transbaikalia are demonstrated to be evolutionarily dualistic. Their composition evolves following the Bowen's reaction series during a single volcanic stage and along the alkali-melanocratic trend (with an increase in the alkalinity and basicity of rocks) within the associations of the initial derivatives of all stages. Both trends are controlled by the crystallization differentiation of basaltic melts at mantle and crustal depth levels.
Keywords: Mesozoic; basalts; Transbaikalia; Mesozoic; Мезозой